(untitled) (Global Journal of Human-Social Science, 2022)
The objective of this article is to analyze the effects of trade opening on food security in the Franc zone with regard to the persistence of food insecurity that is undermining in this zone To do this we have made the assumption that commercial openness improves food security in the franc zone In this work we use a large number of transnational data covering the period 2014-2020 Following the models used by Dithmer and Awudu 2017 and the generalized moments method we have resulted in the result that commercial openness has positive and significant effects on food security This allowed us to confirm our initial hypothesis In view of this outcome governments must set up an observatory to monitor and monitor the opening process in order to ensure that farmers benefit from trade liberalization combined trade policies with well-designed employment and social policies to improve the beneficial effects of openness on food security